Building next-generation converged networks : theory and practice - Pathan, Al-Sakib Khan; Monowar, Muhammad Mostafa; Fadlullah, Zubair Md (CRC Press, 2013)
Supplying a comprehensive introduction to next-generation networks, Building Next-Generation Converged Networks: Theory and Practice strikes a balance between how and why things work and how to make them work. It compiles recent advancements along with basic issues from the wide range of fields related to next generation networks. Containing the contributions of 56 industry experts and researchers from 16 different countries, the book presents relevant theoretical frameworks and the latest research. It investigates new technologies such as IPv6 over Low Power Wireless Personal Area Network (6L.